Biosynthesised AgCl NPs using Bacillus sp. 1/11 and evaluation of their cytotoxic activity and antibacterial and antibiofilm effects on multi‐drug resistant bacteria. Issue 6 (25th April 2018) - Rezaei Somee, Leila; Ghadam, Parinaz; Abdi‐Ali, Ahya; Fallah, Soudabeh; Panahi, Ghodratollah
Abstract : Silver nanoparticles (AgNPs) have attracted the attention of researchers due to their properties. Biological synthesis of AgNPs is eco‐friendly and cost‐effective preferred to physical and chemical methods, which utilize environmentally harmful agents and large amounts of energy. Microorganisms have been explored as potential biofactories to synthesize AgNPs. Bacterial NP synthesis is affected by Ag salt concentration, pH, temperature and bacterial species. In this study, Bacillus spp., isolated from soil, were screened for AgNP synthesis at pH 12 with 5 mM Ag nitrate (AgNO3 ) final concentration at room temperature. The isolate with fastest color change and the best ultraviolet‐visible spectrum in width and height were chosen as premier one. AgNO3 and citrate salts were compared in terms of their influence on NP synthesis. Spherical Ag chloride (AgCl) NPs with a size range of 35–40 nm were synthesized in 1.5 mM Ag citrate solution. Fourier transform infrared analysis demonstrated that protein and carbohydrates were capping agents for NPs. In this study, antimicrobial and antitumor properties of the AgNP were investigated. The resulting AgCl NPs had bacteriostatic activity against four standard spp. And multi‐drug resistant strain of Pseudomonas aeruginosa . These NPs are also cytotoxic to cancer cell lines MCF‐7, U87MG and T293.